Micropropagation of Some Edible Bamboo Species and Molecular Characterization of the Regenerated Plants - Brar, Jasmine (My University, 2014)
The present study was conducted on three important edible bamboo species namely Dendrocalamus membranaceus, Bambusa balcooa and B. bambos which have been listed as priority species by International Union for Conservation of Nature (IUCN) with an aim to establish an efficient and reproducible protocol for their large scale multiplication under in vitro conditions. The other objective was to assess the genetic fidelity of in vitro raised plants by molecular markers and to study their field performance. A comparative evaluation of various physiological and biochemical parameters was carried out to compare in vitro plants with hardened ex vitro plants.
PHD, DBTS
Keywords: micropropagation; genetic fidelity; field performance; molecular markers